1980
DOI: 10.1159/000259996
|View full text |Cite
|
Sign up to set email alerts
|

Phonological Processes in Speech Addressed to Children

Abstract: This experiment was designed to examine the degree of phonological reduction in speech directed at children by adults, as opposed to speech directed at other adults. 8 British mothers were recorded speaking to their 2- to 4-year-old children and to adults in a relaxed home environment. The recordings were analyzed with respect to number of applications of four commonly used phonological rules. It was found that speech to children shows significantly greater phonological reduction in most cases. It is hypothesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
39
0
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(41 citation statements)
references
References 0 publications
1
39
0
1
Order By: Relevance
“…One of the characteristics of spontaneous speech, it will be recalled, is the high frequency of phonological elisions and assimilations (G. Brown 1977, Labov 1972, Milroy 1980. Some studies have reported that child-directed speech, too, is replete with such distorting processes (Bard andAnderson 1983, 1991;Shockey and Bond 1980) which is consistent with the view that this style of speech lies on a general continuum with adult-directed casual speech. Other studies, however, have reported lower frequency of distorting phonological transformations in speech to infants than in speech to adults (Bernstein-Ratner 1984a,b).…”
Section: The Infant's Speech Environmentsupporting
confidence: 63%
“…One of the characteristics of spontaneous speech, it will be recalled, is the high frequency of phonological elisions and assimilations (G. Brown 1977, Labov 1972, Milroy 1980. Some studies have reported that child-directed speech, too, is replete with such distorting processes (Bard andAnderson 1983, 1991;Shockey and Bond 1980) which is consistent with the view that this style of speech lies on a general continuum with adult-directed casual speech. Other studies, however, have reported lower frequency of distorting phonological transformations in speech to infants than in speech to adults (Bernstein-Ratner 1984a,b).…”
Section: The Infant's Speech Environmentsupporting
confidence: 63%
“…Shockey and Bond (1980) in speech to 2-to 4-year-old children and speech to adults. They found that in British English, mothers use single segment phonological reduction more when speaking to their child than when speaking to an experimenter.…”
mentioning
confidence: 96%
“…However, these reports on phonetic reduction in infant-and child-directed speech investigated either word duration or emphasis (Bortfeld & Morgan, 2010;Fisher & Tokura, 1995;Pate & Goldwater, 2011), mild reduction processes in speech directed at toddlers (Shockey & Bond, 1980), they did not provide quantitative data on reduction degree and frequency Anderson, 1983, 1994;Stoel-Gammon, 1984) or focused on read instead of spontaneous speech (Dilley et al, 2013). Hence, they did not study the occurrence of pronunciation variants that are so reduced when compared to their full form that they could be classified as different words by infants.Moreover, several of these studies Anderson, 1983, 1994;Shockey & Bond, 1980) focused on speech directed at children who have already developed lexical representations for a large number of words. Importantly, degree of reduction may change across age or developmental stage of the child, like many other variables in infant-directed speech (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Final consonant deletion is a common feature of typically developing children's speech until the age of three (Grunwell, 1997). Additionally, final consonant devoicing occurs in many languages (Locke, 1983), and in some languages, word-final consonants have disappeared over time (Hock, 1975, cited in Locke, 1983, or have been partially replaced by glottal stops.For example, Shockey and Bond (1980) found that British mothers replaced wordfinal [t] with a glottal stop 44% of the time while talking to their children. In line with these indications, adults are more likely to confuse newly learnt words that differ word finally than word initially, indicating less focus on word final consonants (Creel & Dahan, 2010).…”
mentioning
confidence: 99%